Urbanisation versus agriculture: a comparison of local genetic diversity and gene flow between wood mouse Apodemus sylvaticus populations in human‐modified landscapes. Issue 1 (23rd April 2015) - Wilson, Amanda; Fenton, Brian; Malloch, Gaynor; Boag, Brian; Hubbard, Steve; Begg, Graham
Abstract : Urbanisation and agriculture dramatically modify the landscapes available for use by wildlife, affecting key aspects of their ecology such as survival, foraging, predation, competition and reproductive success. Relatively little is known about the effects of urbanisation and agriculture on the genetic structure, gene flow and genetic diversity of wild species. Here, landscape genetic techniques were applied to compare local genetic diversity and gene flow between wood mouse populations in urban and arable landscapes. Using nine microsatellite markers, individuals were genotyped from six arable and seven urban sample sites. Inter‐population genetic differentiation was significantly greater in urban than arable habitat, while allele richness, private allele richness and heterozygosity were higher for arable sample sites, with varying degrees of significance. These suggest that urban habitat was sufficiently fragmented to limit gene flow. To test the effect of landscape features on gene flow, several cost‐distance measures were generated. Overland distance and Euclidean distance correlated best with inter‐population genetic differentiation in arable habitat, whereas distances that accommodated differences in habitat quality better explained differentiation in urban habitat. There was no evidence that margins adjacent to roads, rivers or railways facilitated gene flow. Together, the results indicate that urban landscapes expose wood mice to greater fragmentation in habitat quality than arable areas, leading to greater population isolation that is not mitigated by the presence of dispersal corridors.